2021
DOI: 10.1371/journal.pone.0249438
|View full text |Cite
|
Sign up to set email alerts
|

DHA but not EPA induces the trans-differentiation of C2C12 cells into white-like adipocytes phenotype

Abstract: Muscle derived stem cells (MDSCs) and myoblast play an important role in myotube regeneration when muscle tissue is injured. However, these cells can be induced to differentiate into adipocytes once exposed to PPARγ activator like EPA and DHA that are highly suggested during pregnancy. The objective of this study aims at determining the identity of trans-differentiated cells by exploring the effect of EPA and DHA on C2C12 undergoing differentiation into brown and white adipocytes. DHA but not EPA committed C2C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
1
2
1
Order By: Relevance
“…Per our knowledge, this the first study investigating the effect of maternal diet enriched with EPA and DHA on fetal muscle development especially during the prenatal stage when de novo myogenesis process is initiated and during early postnatal stage when fully mature myofibers are formed. Our in vivo results were inconsistent with many in vitro studies including our previous ones which referred to the potential differentiation of C2C12 myoblasts into white adipocytes like phenotypes ( Ghnaimawi et al, 2019 ; Hsueh et al, 2018 ; Peng et al, 2012 ; Zhang et al, 2019 ; Lacham-Kaplan et al, 2020 ; Ghnaimawi et al, 2021 ; Ghnaimawi et al, 2020 ). A transient increase in the expression levels of, MtoD1, MRF4, MyoG, and MHC4 was detected in the group fed EPA and DHA enriched diet at D1 ( Figure 3 ) without any change in muscle mass ( Figure 4 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Per our knowledge, this the first study investigating the effect of maternal diet enriched with EPA and DHA on fetal muscle development especially during the prenatal stage when de novo myogenesis process is initiated and during early postnatal stage when fully mature myofibers are formed. Our in vivo results were inconsistent with many in vitro studies including our previous ones which referred to the potential differentiation of C2C12 myoblasts into white adipocytes like phenotypes ( Ghnaimawi et al, 2019 ; Hsueh et al, 2018 ; Peng et al, 2012 ; Zhang et al, 2019 ; Lacham-Kaplan et al, 2020 ; Ghnaimawi et al, 2021 ; Ghnaimawi et al, 2020 ). A transient increase in the expression levels of, MtoD1, MRF4, MyoG, and MHC4 was detected in the group fed EPA and DHA enriched diet at D1 ( Figure 3 ) without any change in muscle mass ( Figure 4 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we demonstrated that maternal supplementation of EPA and DHA induced excessive infiltration of intramuscular fat through up-regulation of PPARγ and other adipogenesis regulatory genes. However, the adipogenic effect was not on the expense of myoblasts as having been reported by several in vitro studies ( Peng et al, 2012 ; Hsueh et al, 2018 ; Ghnaimawi et al, 2019 ; Zhang et al, 2019 ; Ghnaimawi et al, 2020 ; Lacham-Kaplan et al, 2020 ; Ghnaimawi et al, 2021 ). Otherwise, it was mediated by PPARγ activation, ectopically expressed in muscle cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Liu et al found that DHA-PC inhibited angiogenesis through activating PPARγ in endothelial cells [ 28 ]. Ghnaimawi et al confirmed that DHA treatment activated PPAR to promote the transdifferentiation of C2C12 cells into adipocyte phenotypes [ 29 ]. Similarly, the cytotoxicity of DHA on many tumor cells is related to the activation of PPARγ.…”
Section: Discussionmentioning
confidence: 99%